Exploring The Selfie Phenomenon: Identity Representation in Middle School Female Students. - Horwitz, Alexa B. (Tufts Archival Research Center, 2016)
This present study investigated how Middle School female students use selfies to represent identity. The study aimed to understand why this demographic takes selfies and how they share these images of themselves with their peers. The thirteen participants for this study were recruited from the greater Boston area. Interviews were conducted with the participants and the responses were then coded and analyzed using a thematic analysis. Results from the findings pointed to status updates, physical appearance, dialogue, and individual/group positioning as four reasons that motivate middle school girls to take and share selfies. In addition, this study provides a foundation for understanding several social norms relating to middle school female students’ relationship with selfies. This thesis specifically explores those social norms relating to the dialogue these girls use while referring to their peers’ selfies and the expectation that this dialogue will be instantaneous. The results of this study suggest that in future studies, researchers should continue to explore the relationship between emerging digital trends and identity representation through the malleability of images and perceptions of those posting and manipulating them.